The Family Peer Effect on Mothers' Labour Supply - Cheti Nicoletti; Kjell G. Salvanes; Emma Tominey (Institute for the Study of Labor (IZA), 2016)
The documented historical rise in female labour force participation has flattened in recent decades, but the proportion of mothers working full-time has steadily increased. We provide the first empirical evidence that the increase in mothers' working hours is amplified through the influence of family peers. Using Norwegian administrative data we study the long-run influence of the family network on mothers' labour decisions up to seven years post birth. For identification, we exploit partially overlapping peer groups and assume that a mother interacts with her neighbours and family but not with her family's neighbours. We explore mechanisms including information and imitation.
Keywords: D85; C21; C26; 330; peer effects; family network; sibling spillover effects; cousins spillover effects; instrumental variable estimation